Research trends of Islamic Communication and Broadcasting (KPI) students and challenges of Islamic communication science - Usman Usman; Abdul Manan; Yummil Hasan (Islamic Communication Journal, 2022)
The scientific development of Islamic communication is determined by research based on Islamic values. However, the challenge is that Islamic communication deals with established general communication sciences. This study aims to see trends in the research direction of Islamic Communication and Broadcasting Study Program students and its position in the development of Islamic communication science. This study uses a type of qualitative study conducted at the Department of Islamic Communication and Broadcasting, Faculty of Da'wah and Communication Studies, UIN Imam Bonjol Padang with documentation data collection techniques. The objects studied were original documents resulting from student research for the last 5 (five) years totaling 298 titles. The study findings show that 40.98% of students choose mass communication and new media studies, only 19.67% choose da'wah communication studies and da'wah scholarship. This certainly has an influence on the scientific construct of Islamic communication. This means that the discourse on communication science is still dominated by "secular" communication studies, there are still few communication studies originating from Islamic teachings.  The implication of this study is the need to encourage the integration of Islamic communication science and general communication science in future KPI student research activities. ***Perkembangan keilmuan komunikasi Islam ditentukan oleh penelitian-penelitian yang berbasis pada nilai Islam. Namun, tantangannya adalah komunikasi Islam berhadapan dengan keilmuan komunikasi umum yang sudah mapan. Studi ini bertujuan untuk melihat kecenderungan arah penelitian mahasiswa Program Studi Komunikasi dan Penyiaran Islam serta posisinya bagi pengembangan keilmuan komunikasi Islam. Studi ini menggunakan jenis kajian kualitatif yang dilakukan di Jurusan Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Ilmu Komunikasi, UIN Imam Bonjol Padang dengan teknik pengumpulan data dokumentasi. Objek yang dikaji adalah dokumen asli hasil penelitian mahasiswa selama 5 (lima) tahun terakhir sebanyak 298 judul.  Temuan studi menunjukkan 40,98% mahasiswa memilih kajian komunikasi massa dan media baru, hanya 19,67% memilih kajian komunikasi dakwah dan keilmuan dakwah. Hal ini tentu memberikan pengaruh terhadap konstruk keilmuan komunikasi Islam. Artinya wacana tentang ilmu komunikasi masih didominasi oleh kajian-kajian komunikasi yang bersifat “sekuler”, masih sedikit kajian-kajian komunikasi yang bersumber dari ajaran agama Islam. Implikasinya, studi ini mendorong perlunya integrasi keilmuan komunikasi Islam dan ilmu komunikasi umum dalam kegiatan riset mahasiswa KPI kedepan.